2021
DOI: 10.3390/ijerph18084183
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of the SME Sector Operations during the COVID-19 Pandemic

Abstract: The subject matter of the article relates to the assessment of the perception of selected types of risk in economic activities of the SME sector, which change their intensity as a result of the outbreak of the COVID-19 pandemic. The current economic downturn is unprecedented and involves many companies and industries that have faced new, previously unknown challenges and threats. The objective of the article is to identify the most important risks and their resources based on the empirical research carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 49 publications
6
39
0
6
Order By: Relevance
“…It is noted that small businesses are faced with an unprecedented negative impact on their operations ( Liguori and Pittz, 2020 ) and are at risk of running out of cash ( Cowling et al, 2020 ). Similarly, it has been found that smaller firms face greater market, economic, financial and operational risks ( Grondys et al, 2021 ), and are likely to reduce R&D and innovation given the crisis ( Roper and Turner, 2020 ). SMEs and start-ups face a ‘strategy/funding chicken-and-egg-problem’ ( Eggers, 2020 : 206), where there are insufficient resources available to pursue strategies that would protect or enhance firm performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is noted that small businesses are faced with an unprecedented negative impact on their operations ( Liguori and Pittz, 2020 ) and are at risk of running out of cash ( Cowling et al, 2020 ). Similarly, it has been found that smaller firms face greater market, economic, financial and operational risks ( Grondys et al, 2021 ), and are likely to reduce R&D and innovation given the crisis ( Roper and Turner, 2020 ). SMEs and start-ups face a ‘strategy/funding chicken-and-egg-problem’ ( Eggers, 2020 : 206), where there are insufficient resources available to pursue strategies that would protect or enhance firm performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Banaitė (2016) demonstrated that circular economy decreased the use of natural resources, while the consumption of energy rose, leading to increasing pollution (Ionescu, 2020;Nekmahmud et al, 2020). Beneficially, circular economy has shown to maintain the value of recycled materials, while the generation of waste has been minimized (Bayar et al, 2020;Borocki et al, 2019;Çera et al, 2020;Grondys et al, 2021). To continue as before, the exploitation-production-disposal economy should consume the resources of three planets Earth by 2050 (Stott et al, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Despite its significant contribution to the GDP of the global economy (Obi et al, 2018) and serving the role as a sector absorbing workforce (Ghergina et al, 2020), small and medium enterprises (SMEs) owing to its various limitations such as limited human resources, financial and technological know-how (Smith and Wakins, 2012;Wosche et al, 2017) are vulnerable to the impact of business crisis (Grondys et al, 2021). In line with the vulnerability of the SMEs The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/0972-7981.htm operation against the impact of business risks (Verano and Venturini, 2013;Vladic, 2015), creating an improved risk evaluation methodology suitable for the SMEs is believed to increase their business sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…, 2020), small and medium enterprises (SMEs) owing to its various limitations such as limited human resources, financial and technological know-how (Smith and Wakins, 2012; Wosche et al. , 2017) are vulnerable to the impact of business crisis (Grondys et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%